2012
DOI: 10.1212/wnl.0b013e31826e25ce
|View full text |Cite
|
Sign up to set email alerts
|

Past exposure to neuroleptic drugs and risk of Parkinson disease in an elderly cohort

Abstract: In a French elderly cohort, the risk of probable PD was increased by 3.2-fold after exposure to neuroleptics. This finding suggests the necessity of limiting the use of such drugs in elderly people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 37 publications
2
29
1
2
Order By: Relevance
“…Interestingly, a recent 15-year prospective population-based study has shown that long-term risk of incident PD was increased by 3.2-fold after past exposure to neuroleptics, with only 30% of the cases developing probable PD during the exposure. 18 This supports the hypothesis that neuroleptic exposure represents in itself a risk factor for subsequent development of degenerative PD and suggests new questions on such a relationship, which we aim to address. First, are patients who develop DIP during neuroleptic exposure those at increased risk of subsequent PD (suggesting common predisposing factors)?…”
supporting
confidence: 76%
See 3 more Smart Citations
“…Interestingly, a recent 15-year prospective population-based study has shown that long-term risk of incident PD was increased by 3.2-fold after past exposure to neuroleptics, with only 30% of the cases developing probable PD during the exposure. 18 This supports the hypothesis that neuroleptic exposure represents in itself a risk factor for subsequent development of degenerative PD and suggests new questions on such a relationship, which we aim to address. First, are patients who develop DIP during neuroleptic exposure those at increased risk of subsequent PD (suggesting common predisposing factors)?…”
supporting
confidence: 76%
“…Prevalence estimates of umPD according to such studies are unexpectedly high (Table ) and would suggest a causal relationship between neuroleptic exposure and degenerative parkinsonism. Interestingly, a recent 15‐year prospective population‐based study has shown that long‐term risk of incident PD was increased by 3.2‐fold after past exposure to neuroleptics, with only 30% of the cases developing probable PD during the exposure …”
Section: Summary Of the Imaging Studies Detailing Prevalence Estimatementioning
confidence: 99%
See 2 more Smart Citations
“…[67][68][69] In a French elderly cohort of 2,991 noninstitutionalized individuals, neuroleptic exposure increased 3.2-fold the risk to develop probable PD. 70 The risk was significant for benzamides and the calcium channel blockers flunarizine and cinnarizine. The estimated population-attributable fraction of PD associated with drug exposure suggested that avoidance of drug exposure would yield a 21.7% reduction in the number of new cases of PD.…”
Section: Other Clinical Issues Persistent Parkinsonism Following Neurmentioning
confidence: 99%